The express registration of thermal conductivity anomalies of solids - Sokolenko, V.I.; Frolov, V.А.; Savchuk, E.S. (Вопросы атомной науки и техники, 2022)
Investigation of the thermophysical characteristics of materials at low temperatures (T ≤ Θ, Θ is the Debye temperature) makes it possible to obtain information on the interaction of quasiparticles and is in demand in the applied plan. For the indicated temperatures, a method of express registration (ER) of anomalies in the thermal conductivity of solids (k), which is a variation of the classical method of uniaxial stationary heat flux (USHF), but which, unlike the prototype, does not require taking into account heat losses (HL). A feature of the ER method is the measurement of the temperature dependence of the difference δΤ = T₁−T₂ between the ends of the sample under conditions of simultaneous monotonicity of the change in Т of the sample and all HL. In this case, the measured scaled thermal conductivity Ҝ∝(Q/Ψ)/δΤ (Ψ is a monotonic scale factor in T) correlates with the real k∝Q/δΤ. For the interval 300…77 K, one of the variants of the ER method was tested, in which a step-by-step movement of the sample in a column of gaseous nitrogen above the surface of liquid N₂ in a Dewar vessel was used. In the case of a monotonic change in the distance from the sample to the liquid, the formed configuration of isotherms ensures the monotonicity of the change in T of the sample and, at the same time, the monotonicity of the HL along the channels of thermal conductivity and radiation. The possibilities of the ER method are illustrated by examples of determining the temperatures and signs of anomalies in the thermal conductivity coefficients of high-temperature superconductors (HTSC) in the pseudogap state (PGS) and a high-entropy alloy Аl₀.₅CoCuCrNiFе, which is promising for use in the cryogenic temperature range. The method made it possible for the first time to discover the staging of the temperature evolution of the thermal conductivity of YBa₂Cu₃O₇₋ₓ and Bi₁.₆(Pb₀.₄)Sr₂Ca₂Cu₃O₁₀₊ₓ in the PGS and to determine the temperatures and signs of the anomalies. The data obtained convincingly confirmed the results of probing the PGS of HTSCs by the method of polarized neutron scattering carried out with the participation of a number of EU research institutes. Also, for the first time, an extended thermal conductivity anomaly of a high-entropy Аl₀.₅CoCuCrNiFе alloy in the range of ~ 220…170 K was discovered, which is probably a consequence of changes in the configuration of the Fermi surface.